The adult in the room: mobilizing the figure of the child in Sweden and Germany - Brock, Maria; Sundhall, Jeanette; Martinsson, Lena (Frontiers in Political Science, 2025)
This discussion takes as its starting point recent right-wing protests and -rhetoric, forming part of a conservative moral panic surrounding Drag Queen Story Hour (DQSH) and LGBTQ+ pride events, and in particular the harm these are proclaimed to be causing children. While mobilizing the figure of the child for political purposes is not a recent phenomenon, the momentum and number of fellow travelers the instrumentalization of vulnerable innocence of children has achieved recently demand an intervention. The aim of this article is therefore—in conversation with feminist theoretical work, primarily focusing on gender-based needs, to explore specific figures of the child at a time when nationalist right-wing politics are naturalized across multiple domains and geographies. We situate our research at a specific historical and political juncture, with the purpose of enabling a feminist reflection of the categories of childhood and adulthood in order to open them up in potentially empowering ways. We focus on the symbolic and political weight of childhood as a particular age category, analyzing political rhetoric from Germany and Sweden, but speaking to transnational discourses about the child and how it is both transformed and anchored in different national contexts. Importantly, this also means inquiring what it means for some population groups to be forcibly adultified, while being infantilized in other contexts. We conclude that the political use and co-optation of the child in order to mobilize actors arguing that the child is only safe within the confines of traditional values and the ethnonationalist state in fact undermines children’s rights.